2016
DOI: 10.15605/jafes.031.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Activity Level among Patients with Type 2 Diabetes Mellitus at the UP–Philippine General Hospital Diabetes Clinic

Abstract: Introduction. Physical activity is an important factor in reducing morbidity from type 2 diabetes mellitus and maintaining quality of life. There is no available data on physical activity among Filipino patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In relation to metabolic control, our results showed that the low level of PA was significantly correlated with higher HbA1c values. These results are similar to those obtained by Palermo et al in the Philippines [28] . However, another study performed in Oman reported no differences in the metabolic control of physically active patients [14] .…”
Section: Discussionsupporting
confidence: 93%
“…In relation to metabolic control, our results showed that the low level of PA was significantly correlated with higher HbA1c values. These results are similar to those obtained by Palermo et al in the Philippines [28] . However, another study performed in Oman reported no differences in the metabolic control of physically active patients [14] .…”
Section: Discussionsupporting
confidence: 93%
“…10 In a cross sectional study done by Palermo among adult patients diagnosed with T2DM seen at the PGH diabetes outpatient clinic during the study period of 6 months from September 2015 to February 2016 revealed that there is no significant association between physical activity, age, occupation, education. 9 In a cross sectional study done by Patil among adult patients attending the Indira Gandhi government medical college, older age was associated with less physical activity (p<0.01) and educational status was not associated with physical activity (p value 0.12). 4 In an analytical observational study done among type 2 diabetic patients attending the Diabetes Center of Hamadan by Fattahi the age and education was associated with physical activity (p<0.001) and occupation was not associated with physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…In a cross sectional study done by Palermo among type 2 diabetic patients showed that most of the patients had poor glycaemic control based on HbA1c of ≥7% (68.2%). 9 Shazwani…”
Section: Discussionmentioning
confidence: 99%
“…According to type of physical exercise the highest percentage of the patients (14(46.7%) work walking as exercise, concerning the how long do you exercise in day the highest percentage of the patients (23 (76.7%) use 30< min in day as exercise. Palermo and Sandoval (2016) revealed that the majority of the patients in UP-PGH Diabetes Clinic had moderate to high physical activity (68.9%). A higher percentage of subjects aged 60 years and above (68.1%; p=0.022) and with poor glycemic control (89.4%; p=<0.001) had low physical activity level as compared to subjects aged 30 to 59 years (31.9%) and with good glycemic control (10.6%) respectively.…”
Section: Discussionmentioning
confidence: 99%